How New Data Tools Can Assess Climate Risks - Swann, Stacy; Miller, Alan (International Finance Corporation, Washington, DC, 2018)
Climate change doesn’t just threaten the environment, it poses risks to a country’s businesses and economy. Understanding these risks can be complex, yet there are a growing number of tools that can help businesses analyze how their operations will be affected. In order to integrate climate risk into their overall risk management models, companies will need a thorough understanding of how climate change can affect them. With it, they can then then take steps to build resilience into operations.